What is in a Name? Information, Heterogeneity, and Quality in a Theory of Nested Names. (9th November 2017) - Yu, Jianyu; Bouamra-Mechemache, Zohra; Zago, Angelo
Abstract : Collective labels are widespread in food markets, and are either separated or nested with private brands—the latter are known as "nested names". We propose a model to explain the rationale of nested names, with collective labels being effective in reaching unaware consumers, while individual brands help firms to reach aware consumers. We also incorporate decision-making within the group of producers joining collective labels, taking into account their heterogeneity in providing quality. We show that nested names emerge when consumers become more aware of information on the label's quality, as well as when producers become more heterogeneous. Welfare may decrease, however, when the group switches to nested names because they may lead to lower quality incentives for the majority of producers. Our results also provide insights into the historical and recent trends in food industries, such as within-label differentiation and label fragmentation, as well as their respective welfare implications.